Moon Girl and Devil Dinosaur. Vol. 7, Bad dream - Montclare, Brandon (Marvel Worldwide, Inc., 2019)
First, Moon Girl and Devil Dinosaur help protect Christmas, then, the pair are forced to navigate the Dream Dimension where monsters dwell just outside our consciousness. The two finally realize what Bad Dream is up to and require a little help from Doctor Strange.